Safety and effects of scorpion-derived antimicrobial peptides as an alternative to antibiotic growth promoters in broilers: growth performance, immune function, and intestinal development - Gao, Mingyang; Wang, Zhengli; Zhao, Hongfeng; Li, Zihui; Shen, Hong (Frontiers in Veterinary Science, 2025)
Antimicrobial peptides (AMPs) derived from scorpion venom have emerged as promising environmentally sustainable feed additives due to their biosafety and ability to metabolize into natural amino acids without residues. This study investigates IsCT, a cytotoxic peptide from Isometroides scorpions, for its potential application in yellow-feathered broiler production. The study began with in vitro antimicrobial susceptibility testing against major livestock pathogens (Staphylococcus aureus ATCC 6538, Salmonella typhimurium ATCC 14028, Escherichia coli ATCC 25922, and Streptococcus agalactiae ATCC 13813), followed by biosafety evaluations using chicken erythrocytes and Kunming mice. A feeding trial with 360 broilers assigned birds to six dietary treatments: basal diet control, IsCT supplementation at 25, 50, 100, or 200 mg/kg, and a ciprofloxacin control (50 mg/kg). IsCT exhibited concentration-dependent antibacterial activity with no hemolytic effects and demonstrated biosafety in murine models. During days 1–21 and 22–42, IsCT supplementation significantly improved feed conversion efficiency, carcass quality, immunoglobulin levels, and intestinal development in broilers. IsCT shows broad-spectrum efficacy and growth-promoting potential, supporting its use as a sustainable feed additive in yellow-feathered broiler production systems.